COVID-19 and the resilience of European firms: The influence of pre-crisis productivity, digitalisation and growth performance - Mercedes Teruel; Sofia Amaral-Garcia; Péter Bauer; Alexander Coad; Clemens Domnick; Péter Harasztosi; Rozália Pál (European Investment Bank (EIB), 2022)
We analyse how the COVID-19 crisis impacted firms' employment levels and digitalisation efforts differently depending on their pre-crisis productivity, digitalisation and growth performance. We match the EIB Investment Survey with firm-level financial statements from the ORBIS database for 27 EU Member States and the United Kingdom. Following the sales decline during the crisis, we show that: (1) Higher productivity firms are less prone to reduce the number of employees both in the short and in the long term; (2) High-growth enterprises are also less prone to reduce the number of employees in the long term; (3) Firms in highly digitalised sectors are less likely to reduce the number of employees; (4) Firms are more likely to increase their use of digital technologies, especially those that were already more digitalised before the crisis.
Keywords: L22; O47; 330; HGE; labour productivity; digitalisation; COVID-19; Mercedes Teruel; Sofia Amaral-Garcia; Peter Bauer; Alex Coad; Clemens Domnick; Péter Harasztosi; Rozália Pál